Planting - FMO (John Deere, 1992)
This book deals with a number of important functions that the planter must perform: Open a furrow in the soil; Meter the seed; Place the seed; Cover the seed; Firm the seedbed. The devices which perform these functions are briefly discussed in this book; their operation will be described in more detail in later sections of the book